Nghiên cứu mô hình và tối ưu hóa tổng hợp bột nano TiO2 bằng phương pháp thủy phân trong pha hơi. - Thắng, Cao Xuân; Thiêm, Phạm Văn; Xá, Nguyễn Văn; Hà, Mai Ngọc; Anh, Nguyễn Thị Vân (Vietnam Journal of Chemistry, 2012)
Synthesis of metal oxide nano-sized and micro-sized particles by chemical vapor-phase route is a technologically and commercially competitive process. Linking reactor operation parameters to the particle properties represents the most critical task in designing such process. Nanometer sized titania particles were prepared by hydrolysis in gas phase of titanium tetrachloride (TiCl4) in a furnace type aerosol reactor, which is valid at high conversion, was found to be improper at high concentration and low conversion. The TiO2 nano-particles are crystallized in anatase and rutile phase depending on the experimetnal conditions. The size varies from 10 nm to 100 nm. The main advantage of the process is operating at lower temperature (150oC - 400oC) and using water vapour instead of pure oxygen as in the existing chloride process. The explanation of the relationship between TiO2 particle characteristics and the process conditions, a mechanism of nucleation and particle growth will be done. The different methods as XRD, SEM, TEM, micro- Raman, size particles distribution were used to characterize the TiO2 nano-powder in order to find the optimal conditions for the TiO2 fabrication process in aerosol reactor.